ChemInform Abstract: E, Z‐Stereodivergent Synthesis of N‐Tosyl α, β‐Dehydroamino Esters via a Mukaiyama—Michael Addition. Issue 24 (27th May 2016) - Espinosa, Miguel; Garcia‐Ortiz, Andrea; Blay, Gonzalo; Cardona, Luz; Munoz, M. Carmen; Pedro, Jose R.
Abstract: by reaction of silylketene acetals with N‐tosylimines derived from β, γ‐unsaturated α‐ketoesters